HAK MEMILIH ALAT KONTRASEPSI PERSPEKTIF GENDER DAN HUKUM ISLAM - Kms Al Fathur Ihsan; Syahril Jamil; Sandy Wijaya (Usroh: Jurnal Hukum Keluarga Islam, 2021)
Using of the contraceptives in household cases between husband and wife is still a gender gap, as the impact of contraceptive use causes some repercussions for some womenFrom this background, the writer formulates the problem as follows: What are the obstacles in choosing contraceptives for married couples from a gender perspective? What is the perspective of Islamic law on the right to choose contraceptives for married couples. The research method is normative research. Data collection is carried out by a library process, namely through research originating from laws and regulations, books, official documents, publications, and research results, the data is analyzed descriptively qualitatively, then conclusions are drawn using the deductive method, namely drawing conclusions from general to specific. The obstacle in choosing contraceptives was due to the inappropriate number of contraceptives for men and women, namely two versus five. Program policy makers were not yet gender sensitive and women did not have the power to decide contraceptive methods, resulting in dependence on husband's decisions. The perspective of Islamic law on the right to choose contraception is permissible as long as it has the motivation to regulate the birth spacing in order to create a sakinah mawaddah warahmah family Keywords: Keluarga Berencana, Contraceptive Devices, Islamic Law